Can we improve transthoracic echocardiography training in non-cardiologist residents? Experience of two training programs in the intensive care unit - Labbé, Vincent (Ann Intensive Care, 2016)
BACKGROUND: To evaluate the diagnostic performances of two training programs for residents with no prior ultrasound experience to reach competences in extended basic critical care transthoracic echocardiography (CCE) including Doppler capabilities. METHODS: This is a prospective observational study in two intensive care units of teaching hospitals. Group I (five residents) completed a short training program (4-h theory; 3-h practical); group II (six residents) completed a longer training program (6-h theory; 12-h practical). The residents and an expert examined all patients who required a transthoracic echocardiography. Their agreement studied by Cohen’s κ coefficient, concordance coefficient correlation (CCC) and Bland–Altman plots was used as an indicator of program effectiveness. RESULTS: Group I performed 136 CCEs (mean/resident 27; range 22–32; 65 in ventilated patients) in 115 patients (62 men; 64 ± 18 years; Simplified Acute Physiologic Score [SAPS] II 37 ± 18). Group II performed 158 CCEs (mean/resident 26; range 21–31; 65 in ventilated patients) in 108 patients (64 men; 58 ± 17 years; SAPS II 42 ± 22). Both groups adequately assessed left ventricular (LV) systolic function (κ 0.75, 95 % confidence interval [CI] 0.64–0.86; κ 0.77, 95 % CI 0.66–0.88, respectively) and pericardial effusion (κ 0.83, 95 % CI 0.67–0.99; κ 0.76, 95 % CI 0.60–0.93, respectively). Group II appraised severe right ventricular dilatation and significant left-sided valve disease with good to very good agreement (κ 0.80, 95 % CI 0.56–0.96; κ 0.79, 95 % CI 0.66–0.93, respectively). Regarding left ventricular ejection fraction, E/A ratio, E/e′ ratio and aortic peak velocity assessed by group II, CCCs were all >0.70 and the bias (mean difference) ±SD on Bland–Altman analysis was 1.3 ± 8.8 %, 0 ± 0.3, 0.4 ± 2.2 and 0.1 ± 0.4 m/s, respectively. Detection of paradoxical septum (κ 0.65, 95 % CI 0.37–0.93), of heterogeneous LV contraction (κ 0.49, 95 % CI 0.33–0.65) and of respiratory variation of the inferior vena cava (κ 0.27, 95 % CI 0.09–0.45), as well as stroke volume measurement (CCC 0.65, 95 % CI 0.54–0.74; bias ± SD −1.4 ± 4.7 cm), was appraised by group II with moderate agreement requiring probably more comprehensive training. CONCLUSIONS: Although a training program blending 6-h theory and 12-h practical may be adapted to achieve some essential competences, it seems to be insufficiently to perform a complete extended basic critical care transthoracic echocardiography including Doppler capabilities. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/s13613-016-0150-8) contains supplementary material, which is available to authorized users.